Ammonium sulfate improves sensitivity and avoids false negatives of polymerase chain reaction (PCR) for scale drop disease virus (SDDV) detection - Naruporn Rungrueng (2022)
Accuracy is crucial for polymerase chain reaction (PCR) diagnostic laboratories. We noticed inconsistent PCR results or false negatives that sometimes occurred when changing commercial brand of Taq DNA polymerase enzyme. Here, we tested 6 primer sets specific for 3 important aquaculture viruses (scale drop disease virus (SDDV), tilapia lake virus (TiLV), and white spot syndrome virus (WSSV)) using 7 brands of Taq DNA polymerase enzymes (RBC Bioscience, Invitrogen, PCRBiosystems, Bio-Helix, biotechrabbit, GeneAll, and New England BioLabs) with their original reaction buffers. False negative detection and variation in sensitivity of 10–1000 times were observed. Interestingly, only enzymes from RBC Bioscience and Invitrogen could amplify SDDV 252 bp products, while 5 other brands failed to do so. The use of reaction buffer from RBC Bioscience with Taq polymerase enzymes from other brands resulted in improvement of detection sensitivity and avoided false negatives. Comparison of ingredients of the 7 reaction buffers indicated that bovine serum albumin (BSA) and ammonium sulfate were present in the RBC Bioscience buffer but absent or not specified in 6 other brands. Subsequently, we found that adding ammonium sulfate to the original buffers of the 4 selected brands improved detection efficiency for most test reactions, while adding BSA alone or BSA plus ammonium sulfate showed no or little improvement. When tested with serial dilutions of DNA extracted from 2 SDDV-infected fish, adding ammonium sulfate into the original buffer of biotechrabbit brand could improve detection sensitivity 100 times, equal to the result of RBC Bioscience kit. We thus recommend that PCR reaction buffer with ammonium sulfate (10 mM) added might improve detection sensitivity and avoid false negative results in PCR detection assays.